2021
DOI: 10.1111/nep.13948
|View full text |Cite
|
Sign up to set email alerts
|

Potential determinants of the E/e′ ratio in non‐dialysis compared with dialysis patients

Abstract: Aim We hypothesized that arterial function and N‐terminal natriuretic peptide (NT‐proBNP) levels as a marker of volume overload, relate differently to E/e′ as an index of diastolic function in dialysis compared with non‐dialysis patients with chronic kidney disease. We further examined whether cardiovascular risk factors attenuated these relationships. Methods We assessed cardiovascular risk factors and determined arterial function indices by applanation tonometry using SphygmoCor software and E/e′ by echocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 39 publications
2
13
1
Order By: Relevance
“…Our study design was previously reported. [10][11][12][13] Briefly, 46 consecutive black CKD participants including 19 non-dialysis and 27 dialysis patients were enrolled at the Milpark Hospital in Johannesburg, South Africa. Patients with active infection or/and cancer were excluded.…”
Section: Study Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study design was previously reported. [10][11][12][13] Briefly, 46 consecutive black CKD participants including 19 non-dialysis and 27 dialysis patients were enrolled at the Milpark Hospital in Johannesburg, South Africa. Patients with active infection or/and cancer were excluded.…”
Section: Study Participantsmentioning
confidence: 99%
“…We recorded demographic characteristics, traditional cardiovascular risk factors and cardiovascular events as previously reported [10][11][12][13] and detailed in the Supplementary Data Methods. Mean or distending arterial blood pressure for the peripheral waveform was determined electronically by the SphygmoCor device (see below) and using the formula…”
Section: Baseline Characteristics Including Traditional Cardiovascula...mentioning
confidence: 99%
See 3 more Smart Citations